Case report: ZFYVE19 gene mutation is associated with familial cholestasis - Xue, Mei-Yan; Huang, Ling-Ling; Zhu, Yue-Yong; Zheng, Qi (Frontiers in Medicine, 2025)
The etiology of cholestatic liver disease is complex, with clinical manifestations being nonspecific, and biochemical abnormalities mainly characterized by elevated alkaline phosphatase (ALP) and glutamyl transpeptidase (GGT). Due to the lack of specific symptoms and diverse causes, the diagnosis poses certain challenges. Here, we present a case of liver cirrhosis with predominant cholestatic features of unknown etiology. Despite multiple comprehensive routine etiological screenings and liver biopsies, the diagnosis remained unclear. Subsequent whole exome sequencing revealed the diagnosis of liver cirrhosis caused by familial cholestasis related to a mutation in the ZFYVE19 gene. Through this case report analysis, we aim to broaden the diagnostic approach for cholestatic liver disease of unknown etiology, identify the cause accurately, and intervene promptly.